2012
DOI: 10.1158/1535-7163.mct-11-0671
|View full text |Cite
|
Sign up to set email alerts
|

212Pb-Radioimmunotherapy Induces G2 Cell-Cycle Arrest and Delays DNA Damage Repair in Tumor Xenografts in a Model for Disseminated Intraperitoneal Disease

Abstract: In pre-clinical studies, targeted radioimmunotherapy using 212Pb-TCMC-trastuzumab as an in vivo generator of the high energy α-particle emitting radionuclide 212Bi is proving an efficacious modality for the treatment of disseminated peritoneal cancers. To elucidate mechanisms associated with this therapy, mice bearing human colon cancer LS-174T i.p. xenografts were treated with 212Pb-TCMC-trastuzumab and compared to the non-specific control 212Pb-TCMC-HuIgG, unlabeled trastuzumab, and HuIgG, as well as untreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 44 publications
2
43
0
Order By: Relevance
“…Targeting LS-174T tumors with 212 Pb-trastuzumab increases DNA double-stranded breaks, impairs DNA damage repair, persistent G2/M arrest and chromatin remodeling. 9,10 HER2 is expressed by an array of epithelial cancers such as pancreas (35-45%), breast (25-30%), ovarian (25-100%) and colorectal (up to 90%). [11][12][13][14] Conversely, one might also state that HER2, for example, is not well expressed in 55-65% of pancreatic cancers, and therefore identification of additional molecular targets is warranted to expand the repertoire of a-targeted RIT.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting LS-174T tumors with 212 Pb-trastuzumab increases DNA double-stranded breaks, impairs DNA damage repair, persistent G2/M arrest and chromatin remodeling. 9,10 HER2 is expressed by an array of epithelial cancers such as pancreas (35-45%), breast (25-30%), ovarian (25-100%) and colorectal (up to 90%). [11][12][13][14] Conversely, one might also state that HER2, for example, is not well expressed in 55-65% of pancreatic cancers, and therefore identification of additional molecular targets is warranted to expand the repertoire of a-targeted RIT.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, recent reports from this laboratory have also demonstrated effects of nonspecifically targeted a-radiation at the molecular level. 24,37 As of yet, 212 Pb RIT exploiting trastuzumab as the targeting vector has demonstrated great potential as a single agent and in combination with chemotherapeutics possessing three distinct modes of action. The relevance of these combined modalities has to cancer patient management is even greater and more poignant.…”
Section: Discussionmentioning
confidence: 99%
“…The tumors were collected and processed following the previously described procedures. 24 Cell cycle distribution and DNA synthesis were determined by flow cytometry as described with some modifications. 25 Tumors were fixed in cold 70% ethanol, washed in PBS, minced, and incubated in 1 mL 0.04% pepsin (Sigma) w/v in 0.1 N hydrochloric acid (HCl; Mallinckrodt, Inc.) for 1 hour at 37°C with shaking.…”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…Friesen et al studied the efficacy of alpha emitter 213 Bi labeled anti-CD45 antibody in radio-and chemo-resistant leukemia cells [105]. Using DNA ligase IV deficient cells, it was shown that alpha radiation induced slightly more apoptotic cells in lig.IV Pb labeled Trastuzumab [10]. The activation of DNA DSB repair pathways after antibody delivered alpha radiation is not completely the same as that after high LET ion beam radiation.…”
Section: Dna Dsb Repair After High Let Radiationmentioning
confidence: 99%
“…The first human trial of alpha-particle emitter labeled antibody was reported in 1997 wherein alpha emitter 213 Bi labeled anti-CD33 monoclonal antibody HuM195 was investigated in patients with myeloid leukemia [7]. Subsequently, additional human trials using other alpha emitter-labeled antibodies have been conducted, including 211 At-anti-tenascin for glioblastoma [8], 225 Ac-HuM195 for myeloid leukemia [9], 212 Pb-Trastuzumab for ovarian cancer [10], 211 At-MX35 F(ab') 2 for ovarian cancer [11] and 213 Bi-substance P for glioblastoma [12].…”
Section: Alpha-particle Radioimmunotherapy and Heavy Ion Beam Therapymentioning
confidence: 99%